2019
DOI: 10.1186/s12931-019-1143-6
|View full text |Cite
|
Sign up to set email alerts
|

Circulating ESM-1 levels are correlated with the presence of coronary artery disease in patients with obstructive sleep apnea

Abstract: Background Endothelial dysfunction is one of the most important early indicators of atherosclerosis in obstructive sleep apnea (OSA) patients. Endothelial cell specific molecules-1 (ESM-1), which is a novel endothelial dysfunction marker that may be linked to cardiovascular disease. We investigated to assess whether circulating ESM-1 levels are correlated with the presence of coronary artery disease (CAD) in patients with OSA. Methods We performed a cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…Li et al [ 119 ], Deckx et al [ 120 ], Ichihara et al [ 121 ] and Paik et al [ 122 ] showed that the SERPINE2, OGN (osteoglycin), AGTR2 and WNT10B promoted cardiac interstitial fibrosis. Cai et al [ 123 ], Mo et al [ 124 ], Sun et al [ 125 ], Martinelli et al [ 126 ], Zhao et al [ 127 ], Assimes et al [ 128 ] and Piechota et al [ 129 ] showed that CCR7, FCN1, ESM1, F8 (coagulation factor VIII), C1QTNF1, ALOX5 and MSR1 were an important target gene for coronary artery disease. STAB2 have been suggested to be associated with venous thromboembolic disease [ 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 119 ], Deckx et al [ 120 ], Ichihara et al [ 121 ] and Paik et al [ 122 ] showed that the SERPINE2, OGN (osteoglycin), AGTR2 and WNT10B promoted cardiac interstitial fibrosis. Cai et al [ 123 ], Mo et al [ 124 ], Sun et al [ 125 ], Martinelli et al [ 126 ], Zhao et al [ 127 ], Assimes et al [ 128 ] and Piechota et al [ 129 ] showed that CCR7, FCN1, ESM1, F8 (coagulation factor VIII), C1QTNF1, ALOX5 and MSR1 were an important target gene for coronary artery disease. STAB2 have been suggested to be associated with venous thromboembolic disease [ 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…Congestive heart failure (CHF) was defined as a previous diagnosis of heart failure combined with the treatment with diuretics (14). Coronary artery disease (CAD) was defined if patients have at least one of the following characteristics: a previous diagnosis of CAD or the presence of ≥ 50% luminal stenosis in at least one major coronary artery in coronary angiography (15). Hypertension (HTN) was defined as systolic blood pressure ≥ 140 mmHg or diastolic blood pressure ≥ 90 mmHg at two or more visits or a past medical history of HTN or the use of antihypertensive medications (16).…”
Section: Definition Of the Explanatory Variablesmentioning
confidence: 99%
“…[63,64] An increased CIMT and reduced FMD are early subclinical indicators of AS. [59] One report included in this research [30] also highlighted significantly higher circulating endocan levels in individuals with OSAHS and comorbid coronary artery disease (CAD) than in those without CAD. These findings suggest that circulating endocan levels may serve as a valuable biomarker for monitoring CAD development and progression in patients with OSAHS.…”
Section: Discussionmentioning
confidence: 99%
“…Among these 28 studies, 16 were excluded; the reasons for exclusion are listed in Figure 1. Ultimately, 12 studies [17,18,[25][26][27][28][29][30][31][32][33][34] were included in the meta-analysis.…”
Section: Study Inclusionmentioning
confidence: 99%